Engineering of inorganic nanoparticles as magnetic resonance imaging contrast agents - Ni, Dalong (Chem Soc Rev, 2017)
Magnetic resonance imaging (MRI) is a highly valuable non-invasive imaging tool owing to its exquisite soft tissue contrast, high spatial resolution, lack of ionizing radiation, and wide clinical applicability. Contrast agents (CAs) can be used to further enhance the sensitivity of MRI to obtain information-rich images. Recently, extensive research efforts have been focused on the design and synthesis of high-performance inorganic nanoparticle-based CAs to improve the quality and specificity of MRI. Herein, the basic rules, including the choice of metal ions, effect of electron motion on water relaxation, and involved mechanisms, of CAs for MRI have been elucidated in detail. In particular, various design principles, including size control, surface modification (e.g. organic ligand, silica shell, and inorganic nanolayers), and shape regulation, to impact relaxation of water molecules have been discussed in detail. Comprehensive understanding of how these factors work can guide the engineering of future inorganic nanoparticles with high relaxivity. Finally, we have summarized the currently available strategies and their mechanism for obtaining high-performance CAs and discussed the challenges and future developments of nanoparticulate CAs for clinical translation in MRI.